Development of Digital-Based Interactive Teaching Materials in Draping Courses - Nurlita, Asri Andarini (Universitas Pendidikan Indonesia (UPI), 2023)
Interactive teaching materials are learning media that combine various formats such as audio, text, images, animations, and interactive videos. Thus, there is a two-way communication between the teaching materials and their users. The purpose of this research is to make interactive teaching materials for draping courses which are expected to produce products in the form of teaching materials that suit the needs of students. The research method used is development research with the stages of designing, producing, evaluating, and analyzing data with percentages. The results of this study indicate that learning media in the form of interactive teaching materials developed in draping courses are appropriate for use in learning. Based on the trial stages, this interactive teaching material is categorized as valid with a feasibility level of 84% with good criteria. This digital-based interactive teaching material is expected to be learning media in draping courses because the presentation of interesting material makes it easy for users to understand, how to access interactive teaching materials is easy, and able to increase user learning motivation.